Combination of Insulin and UC-MSCs Secretome Therapy Demonstrates A Trend of Liver Injury Improvement in Diabetic Metabolic Dysfunction-associated Steatotic Liver Disease (MASLD) Rat Model - Shirly Gunawan; Siufui Hendrawan; Olivia Marcelina; Jennifer Lheman; Hans Ulrich Baer (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Metabolic dysfunction-associated steatotic liver disease (MASLD) coexists with diabetes mellitus and presents a significant therapeutic challenge due to its complex metabolic and hepatic pathology. Insulin therapy remains the cornerstone for glycemic management, but its effects on hepatic steatosis is inconsistent. Complementary therapies are needed to address this limitation. Umbilical cord-derived mesenchymal stem cells (UC-MSCs) secretome has emerged as therapeutic approach for metabolic disease due to its anti-inflammatory, immunomodulatory, and antioxidant properties. This study was conducted to evaluate whether adjunctive administration of UC-MSCs secretome could enhance therapeutic outcomes, particularly in alleviating hepatic steatosis in a diabetic MASLD rat model.METHODS: Male rats were grouped into normal and diabetic MASLD rat model, and treated with either growth medium, insulin, UC-MSCs secretome, or combination of insulin and UC-MSCs secretome for 4 weeks. Blood samples were collected and liver enzymatic and lipid profile were analyzed using chemistry analyzer. Liver tissue was also obtained for assessment of liver fibrosis using Hematoxylin-Eosin staining, interleukin (IL)-6 measurement using enzyme-linked immunosorbent assay (ELISA), and superoxide dismutase (SOD) activity measurement using colorimetry.RESULTS: Combined insulin and UC-MSCs secretome therapy showed a trend toward better blood glucose management and lipid parameters, although not statistically significant. Administration of insulin, secretome, and their combination was associated with higher hepatic SOD levels and lower IL-6 protein levels, although not statistically significant. Combined therapy also reduced hepatomegaly compared to untreated diabetic MASLD rat model, and improved hepatic steatosis while significantly alleviating fibrosis severity.CONCLUSION: Combination of insulin and UC-MSCs secretome therapy in diabetic MASLD was able to improve several parameters related to hepatic steatosis compared with the untreated diabetic MASLD rat model. These findings suggest that UC-MSCs secretome might serve as a potential adjunct to insulin therapy.KEYWORDS: metabolic dysfunction-associated steatotic liver disease, type 2 diabetes, cell free therapy, umbilical cord mesenchymal stem cells, secretome